Altered neurotransmission in stress-induced depressive disorders: The underlying role of the amygdala in depression. (April 2023) - Asim, Muhammad; Wang, Huajie; Waris, Abdul
Abstract: Depression is the second leading cause of disability in the world population, for which currently available pharmacological therapies either have poor efficacy or have some adverse effects. Accumulating evidence from clinical and preclinical studies demonstrates that the amygdala is critically implicated in depressive disorders, though the underlying pathogenesis mechanism needs further investigation. In this literature review, we overviewed depression and the key role of Gamma-aminobutyric acid (GABA) and Glutamate neurotransmission in depression. Notably, we discussed a new cholecystokinin-dependent plastic changes mechanism under stress and a possible antidepressant response of cholecystokinin B receptor (CCKBR) antagonist. Moreover, we discussed the fundamental role of the amygdala in depression, to discuss and understand the pathophysiology of depression and the inclusive role of the amygdala in this devastating disorder.